The Origins and Extent of Entrepreneurial Action-Orientedness: An Experimental Study - Ahmad Barirani; Randolph Sloof; Mirjam van Praag (Tinbergen Institute, 2017)
We test the hypothesis, based on popular and theoretical perspectives, that entrepreneurs are more action-oriented than other occupational groups. We compare their playing strategies in an optimal stopping game using a randomized online experiment among 100s of entrepreneurs, managers and employees. Our experimental results show that entrepreneurs are indeed more action-oriented than others. We theorize that this is driven by their lower levels of loss aversion and higher levels of curiosity. Our empirical test results show that (i) entrepreneurs score indeed higher, on average, than managers and employees on curiosity and lower on loss aversion; (ii) the di fference in action-orientedness between entrepreneurs and others vanishes when controlling for individual curiosity levels and (iii) an alternative treatment that provides subjects with counterfactual information (about what would have happened in case of stopping) increases their willingness to stop. Under some assumptions, the combination of these results leads to the conclusion that the higher action-orientedness of entrepreneurs can be linked to their greater curiosity, but not to their lower level of loss aversion. Hence, we find support for the intuitive idea that (curiosity driven) action-orientedness enhances the identi fication and/or exploitation of opportunities.
Keywords: L26; C93; D03; 330; Entrepreneurs; Managers; Employees; Inaction; Curiosity; Loss aversion; Lab-in-the field experiment